Respuesta :

Neuron
If you would like to find the solutions to the quadratic equation (5y + 6)^2 = 24, you can do this using the following steps:

(5y + 6)^2 = 24
25y^2 + 2 * 6 * 5y + 36 = 24
25y^2 + 60y + 36 - 24 = 0
25y^2 + 60y + 12 = 0
25 * (y + 6/5)^2 - 24 = 0
1. y = -6/5 - (2 * sqrt(6))/5
2. y = (2 * sqrt(6))/5 - 6/5

The correct result would be y = -6/5 - (2 * sqrt(6))/5 and y = (2 * sqrt(6))/5 - 6/5.

The solution to the quadratic equation is y = -2.18 and y = -0.22

How to evaluate the function?

The equation is given as:

(5y + 6)^2 = 24

Expand

25y^2 + 60y + 36 = 24

Subtract 24 from both sides

25y^2 + 60y + 12 = 0

Using a graphical tool, we have the solution to be:

y = -2.18 and y = -0.22

Hence, the solution to the quadratic equation is y = -2.18 and y = -0.22

Read more about quadratic equation at:

https://brainly.com/question/10449635

#SPJ5

ACCESS MORE